The Sixth Pillar of Reading Instruction: Knowledge Development. (18th March 2015) - Cervetti, Gina N.; Hiebert, Elfrieda H.
Abstract: The National Reading Panel (NRP) identified five pillars, or essential components, of reading instruction that lead to the highest chance of reading success—phonemic awareness, phonics, fluency, vocabulary, and comprehension. A decade after the NRP's report, the majority of US states adopted the Common Core State Standards/English Language Arts & Literacy (CCSS/ELA). One of the most significant changes of the CCSS/ELA is a focus on knowledge development as part of literacy development and focus on the acquisition of literacy skills specific to different disciplines. In highlighting these connections between ELA and knowledge as part of literacy, the CCSS/ELA provide an opportunity for teachers to emphasize what research has validated for decades: that knowledge is a critical component of the reading process. In this column, we describe why knowledge development should be viewed as the sixth pillar of reading instruction and how teachers can increase their students' knowledge building through reading.